Triple-site pacing for cardiac resynchronization in permanent atrial fibrillation : acute phase results from a prospective observational study - Marques, Pedro (2019)
© 2016 Sociedade Portuguesa de Cardiologia. Published by Elsevier España, S.L.U. All rights reserved.